Composite membranes of sulfonated poly (Ether ether ketone) with active carbon: Composite preparation and investigation of their properties for potential application for co2 electrochemical reduction - Fedorenko, Deniss; Vaivars, Guntars (Kauno Technologijos Universitetas, 2020)
In this study, synthesis of sulfonated poly(ether ether ketone) (SPEEK) was performed using sulfonation method with concentrated sulfuric acid. Polymer with three degrees of sulfonation was obtained: 0.87; 0.82 and 0.74. Composite membranes were synthesized with an activated carbon. Ultrasonication method was used in order to achieve homogeneity of distribution of the additive in polymer solution and then in polymer membranes. Membranes with various content of the additive were made: 0; 0.15; 0.3; 0.5; 0.6; 0.8; 1.0; 2.0 and 3.0 %. Swelling degree, water uptake, proton conductivity, isoelectric point, thermal properties and surface morphology of the membranes were analyzed. Proton conductivity was determined using impedance analysis with two electrode system and through-plane configuration. Two methods were used: differential and single membrane method. Differential method is proposed to have significant advantage as it reduces contact resistance, which otherwise is difficult to control and evaluate. Surface zeta potential of membrane surface was investigated, and membranes have shown variation of the potential. Isoelectric point was determined for the membranes with DS 0.82 and carbon content 0 % and 0.5 %, and it was found to be at pH 4. Water uptake and swelling degree of the membranes was studied, and active carbon content was found to not have major influence on those properties, but higher content of sulfonic groups leads to increased water uptake and swelling degree. Thermogravimetric analysis showed slightly better thermal properties of membranes with the additive, compared to the blank membranes, which can be related to differences in the water uptake. Surface of the membrane was investigated using scanning electron microscopy, and no considerable defects were observed.
Authors of this work acknowledge funding from European Union`s Horizon 2020 Research and Innovation Program project under grant agreement No 768789.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; CO2 reduction; Impedance analysis; Sulfonated poly(ether ether ketone); Surface zeta potential